If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2X + -2 = (X + -5) Reorder the terms: -2 + 2X = (X + -5) Reorder the terms: -2 + 2X = (-5 + X) Remove parenthesis around (-5 + X) -2 + 2X = -5 + X Solving -2 + 2X = -5 + X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1X' to each side of the equation. -2 + 2X + -1X = -5 + X + -1X Combine like terms: 2X + -1X = 1X -2 + 1X = -5 + X + -1X Combine like terms: X + -1X = 0 -2 + 1X = -5 + 0 -2 + 1X = -5 Add '2' to each side of the equation. -2 + 2 + 1X = -5 + 2 Combine like terms: -2 + 2 = 0 0 + 1X = -5 + 2 1X = -5 + 2 Combine like terms: -5 + 2 = -3 1X = -3 Divide each side by '1'. X = -3 Simplifying X = -3
| 27=r^3 | | 6c+4d= | | 11=-3+2w | | Log^7(-3m-1)=log^7(-4m-6) | | -(1/3)y-6=-11 | | 8.9x+16.46=-11.1x+14.70 | | 4900((38950/4900)-X)=-770 | | 4900((38950/4900)-X)=770 | | 19x1/2 | | (((6.3*220)+(70*12.9))+66)-(28*6.8)=x | | 6(v+2)-2v=2(2v+4)-11 | | (((6.3*x)+(70*12.9))+66)-(31*6.8)=2154 | | 16-(r/7)=21 | | 0.25xY=23 | | F=4log(x/10^-5) | | z^4=6z^2+27 | | -36/15 | | x/0.55-2x | | (-1/12-7/3)/3/13 | | 16+x=-13 | | (-a-4b+2)ab= | | -11=x+22 | | 5a*6=120 | | x^1/4-1=0 | | (((4.3*x)+(70*4.7))+655)-(31*4.7)=2154 | | (((4.3*x)+(71*4.7))+655)-(31*4.7)=2154 | | 3.14=9420 | | 9+2s-7=9s+3-6s | | (((4.3*x)+(70*4.7))+655)-(30*4.7)=2154 | | a-7=-11 | | 4x^2-13x-36=0 | | -4(t-5)-(t+8)=5 |